China's creative industries: Copyright, social network markets and the business of culture in a digital age - Montgomery, Lucy (Edward Elgar Publishing, 2012)
The context in which this book was produced is important, because there’s a great deal more going on here than a simple observation of recent developments in an emergent economy. Lucy Montgomery has synthesized interdisciplinary approaches to the creative economy, media studies, copyright law and ‘area’ studies. In an era of hyper-specialization it is unusual to find such a range of concerns, but at the same time it is impossible to do justice to specialist domains without knowing how they fit together, and how different national economic and cultural systems interconnect in a globalized economy and technologically networked culture.